POSISI MADRASAH DI TENGAH PERUBAHAN SISTEM PENDIDIKAN ISLAM - Djamas, Nurhayati (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
The change of status of Madrasah as public school will not immediately improve the quality of Madrasah. Taken as a competition, the Madrasah institution is the one that had a late start. Nevertheless, the demand is still persistent, that Madrasah be more responsive to the changes. Therefore, if Madrasah does not improve itself and does not make some innovative breakthrough, it will be even farther behind the public school. This article is an at tempt to study the position of Madrasah in the rapidly-changing situation, particularly in response to Undang-Undang Sisdiknas no. 20 of the year 2003.